Implementation of International Financial Reporting Standards in Ukraine - Ruslana Kuzina (Journal of Accounting and Management Information Systems (JAMIS), 2014)
Since Ukraine gained independence in 1991, the Ukrainian economy has been undergoing constant transformation. Legislative, institutional and structural reforms have been driven by the rapidly changing business environment and much progress towards a market economy has been made. The Ukrainian economy now comprises a spectrum of economic subjects, ranging from large financial-industrial groups (FIGs) and banking institutions to small, privately financed enterprises. One necessary precondition for access to such cheaper investment finance is reliable, high quality financial information; thus, the pace and extent of Ukraine's economic reform is being held back by the widespread lack of such information. In this article author describes the evolution of the implementation of International Financial Reporting Standards in Ukraine, makes an attempt to identify some problems of methodological, organizational and practical nature. In this article author describes the evolution of the implementation of International Financial Reporting Standards in Ukraine, makes an attempt to identify some problems of methodological, organizational and practical nature.
Keywords: M41; 650; IFRS studies; Turkey; accounting developments